Enhancing Sustainable Communities through the Protection of Natural Buffer Zones - Faryadi , Masoud (Journal of Sustainable Development Law and Policy, 2025)
Certain regions within Middle Eastern countries are vulnerable to climate-related hazards, including floods and dust storms, resulting in adverse consequences for these nations and hindering the sustainable development of urban communities. The preservation and development of natural buffer zones, such as green spaces and surface waters, offer nature-based solutions to shield urban areas from the impacts of these hazards. This article examines the significance and legal protection of these buffer zones and concludes that, despite their effectiveness in mitigating floods and dust storms, natural buffer zones have not received distinct recognition as protective zones for urban areas in international and national legal frameworks. The study recommends the integration of natural buffer zones preservation and development into national and regional urban planning and disaster risk management policies and strategies, highlighting their role as nature-based solutions for enhancing urban sustainability in the Middle East, especially Iran.